A Novel Reassortant Avian H7N6 Influenza Virus Is Transmissible in Guinea Pigs via Respiratory Droplets - Zhao, Zongzheng; Liu, Lina; Guo, Zhendong; Zhang, Chunmao; Wang, Zhongyi; Wen, Guoyuan; Zhang, Wenting; Shang, Yu; Zhang, Tengfei; Jiao, Zuwu; Chen, Ligong; Zhang, Cheng; et al. (Frontiers in Microbiology, 2019)
Since 2013, H7N9 and H5N6 avian influenza viruses (AIVs) have caused sporadic human infections and deaths and continued to circulate in the poultry industry. Since 2014, H7N6 viruses which might be reassortants of H7N9 and H5N6 viruses, have been isolated in China. However, the biological properties of H7N6 viruses are unknown. Here, we characterize the receptor binding preference, pathogenicity and transmissibility of a H7N6 virus A/chicken/Hubei/00095/2017(H7N6) (abbreviated HB95), and a closely related H7N9 virus, A/chicken/Hubei/00093/2017(H7N9) (abbreviated HB93), which were isolated from poultry in Hubei Province, China, in 2017. Phylogenetic analyses demonstrated that the hemagglutinin (HA) gene of HB95 is closely related to those of HB93 and human-origin H7N9 viruses, and that the neuraminidase (NA) gene of HB95 shared the highest nucleotide similarity with those of H5N6 viruses. HB95 and HB93 had binding affinity for human-like α2, 6-linked sialic acid receptors and were virulence in mice without prior adaptation. In addition, in guinea pig model, HB93 was transmissible by direct contact, but HB95 was transmissible via respiratory droplets. These results revealed the potential threat to public health posed by H7N6 influenza viruses and emphasized the need for continued surveillance of the circulation of this subtype in poultry.